Male fertility during and after immune checkpoint inhibitor therapy: a cross-sectional pilot study - Salzmann, Martin; Tosev, Georgi; Heck, Melanie; Schadendorf, Dirk; Maatouk, Imad; Enk, Alexander; Hartmann, Martin; Hassel, Jessica C. (European journal of cancer, 2021)
Background - Immune checkpoint inhibitors (ICIs) are widely used and may induce long-term survival in various types of cancer. Yet, there is scarce evidence on potential effects on patient fertility and the necessity of cryopreservation before treatment onset. The aim of our study was to assess the prevalence of male infertility after initiation of ICI treatment. - Methods - This is a monocenter, cross-sectional pilot study. Fertility was investigated by spermiogram, analysis of sexual hormones and questionnaires on sexual function and sexual activity. Male patients under the age of 60 years previously or currently treated with ICI for cutaneous malignancies or uveal melanoma were included. - Results - Twenty-five patients were included, with a median age of 49 years. Eighteen of 22 (82%) available spermiograms showed no pathologies, all patients reported a normal sexual function and sexual activity. Of four patients with pathological spermiogram, three patients were diagnosed with azoospermia and one with oligoasthenoteratozoospermia. Three patients had significant confounding factors (previous inguinal radiotherapy, chemotherapy and chronic alcohol abuse, and bacterial orchitis). One patient with normal spermiogram before ICI treatment presented 1 year after initiation with azoospermia, showing an asymptomatic, inflammatory infiltrate with predominantly neutrophil granulocytes, macrophages and T-lymphocytes in the ejaculate. Infectious causes were ruled out; andrological examination was unremarkable. A second case with reduced sperm counts during treatment may be ICI-induced also. - Conclusions - Most patients had no restrictions in fertility, yet an inflammatory loss of spermatogenesis seems possible. Cryopreservation should be discussed with all patients with potential future desire for children before treatment.
Gesehen am 30.09.2021